Response of phosphine-resistant mixed-age cultures of lesser grain borer, Rhyzopertha dominica (F.) to different phosphine-carbon dioxide mixtures. (October 2016) - Manivannan, Selladurai; Koshy, Gisha Elizabeth; Patil, Swati Ashokrao
Abstract: Mixed-age cultures of a phosphine-resistant strain of lesser grain borer, Rhyzopertha dominica (F.) were exposed to various concentrations of phosphine and phosphine plus 10, 20 and 30% carbon dioxide combinations (CO2 ) for different time intervals at 25 °C to evaluate the comparative efficacy of admixtures of phosphine-CO2 . The mortality data of the mixed age cultures were recorded taking the adult count at weekly intervals for 8 weeks. Lethal concentrations were determined by probit analysis. Phosphine with carbon dioxide exerted significant synergistic effect on the mortality of mixed-age cultures at 4, 6 and 7 days of exposure, while individually phosphine or carbon dioxide did not show a raised increase in their response. The addition of 30% carbon dioxide to lower concentrations of phosphine over shorter exposures of 4 days showed better synergistic effect among the treatments. The present study revealed that CO2 augmented the effect of phosphine thereby reducing the concentration and exposure time required to bring about significant mortality in the mixed-age cultures of R. dominica . Highlights: We studied the synergistic effects of PH3 +CO2 on PH3 -resistant, R. dominica. Lethal concentrations for PH3 +CO2 reduced as compared to PH3 alone treatments. Addition of 30% CO2 to PH3 increased mortality with reduced exposure time. Results of the study would be applicable for control of PH3 -resistant, R. dominica.